Effects of surrounding powder in sintering process on the properties of Sb and Mn- doped barium-strontium titanate PTCR ceramics - Pornsuda Bomlai (Songklanakarin Journal of Science and Technology (SJST), 2006)
In this research, the effects of surrounding powder used during sintering of Sb and Mn doped bariumstrontium titanate (BST) ceramics were studied. The ceramic samples were prepared by a conventional mixed-oxide method and placed on different powders during sintering. Phase formation, microstructure and PTCR behavior of the samples were then observed. Microstructures and PTCR behavior varied with the type of surrounding powder, whereas the crystal structure did not change. The surrounding powder has more effects on the shape of the grain than on the size. The grain size of samples was in the range of 5-20 μm. The most uniform grain size and the highest increase of the ratio of ρmax/ρRT were found to be about 106 for samples which had been sintered on Sb-doped BST powder. This value was an order of magnitude greater than for samples sintered on a powder of the equivalent composition to that of the sample pellet.